2020
DOI: 10.5395/rde.2020.45.e23
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial efficacy of QMix on Enterococcus faecalis infected root canals: a systematic review of in vitro studies

Abstract: Objectives: This study aimed to summarize the outcome of in vitro studies comparing the antibacterial effectiveness of QMix with other irrigants against Enterococcus faecalis. Materials and Methods: The research question was developed by using population, intervention, comparison, outcome, and study design framework. The literature search was performed using 3 electronic databases: PubMed, Scopus, and EBSCOhost until October 2019. The additional hand search was performed from the reference list of the eligible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 45 publications
0
11
0
3
Order By: Relevance
“…Qmix®, a formulation of chlorhexidine, EDTA and a detergent, was reported to be more effective than 2% chlorhexidine and MTAD® against planktonic and biofilm forms of E. faecalis [ 152 ]. Its antibacterial effectiveness against E. faecalis was similarly reported on by recent systematic review of in vitro studies [ 153 ]. The recently developed SmearOFF™ likewise contains chlorhexidine, EDTA and a surfactant, however an in vitro study suggested it had poor antibiofilm properties against E. faecalis [ 141 ].…”
Section: Clinical Implications Of Root Canal Infectionsmentioning
confidence: 71%
“…Qmix®, a formulation of chlorhexidine, EDTA and a detergent, was reported to be more effective than 2% chlorhexidine and MTAD® against planktonic and biofilm forms of E. faecalis [ 152 ]. Its antibacterial effectiveness against E. faecalis was similarly reported on by recent systematic review of in vitro studies [ 153 ]. The recently developed SmearOFF™ likewise contains chlorhexidine, EDTA and a surfactant, however an in vitro study suggested it had poor antibiofilm properties against E. faecalis [ 141 ].…”
Section: Clinical Implications Of Root Canal Infectionsmentioning
confidence: 71%
“…Q-Mix consists of bisbiguanide antimicrobial agent (2% chlorhexidine [CHX]), a polyaminocarboxylic acid calcium-chelating agent (17% ethylenediaminetetraacetic acid), and a surfactant (N-cetyl-N, N, N-trimethylammonium bromide-0.001 to about 3.0 weight percent) and deionized water. It has a good effect in smear layer removal, thus, the antimicrobial effect and smear layer removal are done in one step,[ 5 6 ] which allows to shorten the treatment time and finish the treatment in one session. The study of miçooğullari and çalişkan in 2018 found that using of biguanide based irrigant (CHX) as a final irrigation solution and finishing the endodontic treatment in one session had the same effect of using a calcium hydroxide paste as a temporary dressing for 2 weeks regarding postoperative pain and periapical healing.…”
Section: Discussionmentioning
confidence: 99%
“…The superiority of the QMix solution was attributed to its materials that have antibacterial properties and the ability to remove the smear layer at the same time [ 5 ]. The addition of surfactants to QMix 2in1 improved the wettability of this solution and thus improved its ability to penetrate further into the root canal.…”
Section: Discussionmentioning
confidence: 99%
“…The necrotic pulp and periapical lesions contain a large number of polymorphic bacteria [ 5 ]. Enterococcus faecalis (E. faecalis) bacteria has been mentioned with increasing frequency as a serious challenge in endodontic therapy because it is the most common post-endodontic infection.…”
Section: Introductionmentioning
confidence: 99%